Avaliação de eficácia e segurança da acetazolamida na doença periodontal experimental - Ramos, Tercio Carneiro (2010)
Periodontal diseases are the main cause of tooth loss in adults. The preponderant etiologic factor for the onset of periodontitis is the accumulation of dental biofilm with predominance of anaerobic gram negative bacteria. In spite of being of bacterial origin, the inflammatory response induced by factors in the host may influence the progression and clinical characteristics of periodontal disease. Alveolar bone is typical in the development of this pathology and is dependent on osteoclastic activity. In turn, one of the mechanisms of bone resorption by these cells is through the production of protons released in the resorption vacuoles by carbonic anhydrase activity. It has been reported that carbonic anhydrase inhibitors, such as acetazolamide, have a suppressive action on osteoclasts. The aim of this study was to analyze the effect of acetazolamide (ACTZ) on bone loss induced in the experimental periodontitis model in rats, as well as the dosage of seric biomarkers in the periodontal inflammatory process and histologic analysis of the periodontium. Safety analyses were also performed by means of a complete hemogram, biochemical tests for TGP, TGO, gama-GT and histopathology of organs such as: the liver, kidneys, spleen, heart and lungs. To evaluate alveolar bone loss, 50 rats received nylon ligatures in the maxillary left second molar region. The animals were divided into six groups: Vehicle Group (propylenoglycol) (n=9), Positive Control Group (alendronate 0.08 V (n=7), Negative Control Group (saline) (n=6) and Groups that received acetazolamide I.P. in the following doses: (8.3, 25 and 75 mg/Kg [Groups ACTZ8,3, ACTZ25 and ACTZ75 respectively] n= 7, 9 and 9). After 11 days, the rats were sacrificed. Alveolar bone loss was macroscopically evaluated by means of the area of root exposure. In another four groups, ACTZ25 (n=5) and vehicle (n=5), the periodontium was histologically analyzed after 11 and 17 days of ligature, by HE staining. Seric biomarkers were dosed (IL-1, IL-4, fractalkine, CINC-2, CINC-3, LIX, GM-CSF, βNGF, VEGF and CNTF) by means of the microarray technique before and after ligature in three groups; ACTZ25, Vehicle and Sham (simulated surgery). In the ACTZ25 group, safety analysis was performed (alpha=5%). Macroscopically, the alendronate Group (positive control) presented the lowest bone loss, followed by Groups ACTZ75 and ACTZ25 (p<0.05) when compared with the vehicle and saline controls, which did not differ between them (p>0.05). Histologically, the ACTZ group presented the lowest bone and cement resorption (p<0.05) after 17 days of ligature, and there was no difference between the ACTZ25 and vehicle groups with regard to inflammatory infiltrate (P>0.05). The highest concentrations of IL-4 and CNTF were observed in Group ACTZ25 (p< 0.05) when compared with the vehicle group. The safety analyses demonstrated that acetazolamide at the dose of 25 mg/Kg was well tolerated without significant alterations in the hemogram, hepatic enzymes and histopathology of the researched organ. It was concluded that acetazolamide may protect the periodontium from bone resorption induced by ligature in rats, and may be associated with mediators involved in repair, such as IL-4 and CNTF, in addition to being well tolerated.